OPEN AND DISTANCE HIGHER EDUCATION AND RIGHTS OF THE DIFFABLE - Mani Festati Broto (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2009)
This article discusses a qualitative research of diffable in the relation with open and distance education. A summary of in-depth interviews with 5 diffable is presented. It is expected that these interviews will help us gain better understanding of diffable people. Linking the diffabled to distance education, we will see that they are potential students of open and distance higher education institutions.